La question coloniale - Paul Ricœur (Études Ricoeuriennes / Ricoeur Studies, 2021)
In this anti-colonial treatise, Ricœur reflects on the responsibility of every French citizen and of the French state with respect to colonialism. He establishes five principles that should guide his readers in their reflection on this issue and expresses his support for the independence of the colonies.